Strategic planning in Ireland's institutes of technology - Elwood, L.; Rainnie, Al (Palgrave journals, 2012)
This article focuses upon Ireland's institute of technology sector, which has been transformed from a 1970s technical orientation to its broader current role of research and higher education provision. The transformational shifts experienced by institutes over the previous three decades have been profound: increased autonomy, new managerial and organisational paradigms, and demands for greater transparency, accountability and responsiveness. The legislative requirement on these institutes to publish 5-year strategic plans is seen by Ireland's higher education policy makers as a critical planning and coordinating mechanism; yet little empirical work exists on the degree of alignment engendered by strategic planning among academics and manager-academics. Through an exploration of the experiences of these stakeholders in four institutes, this research reveals a dilemma for Ireland's higher education policy makers; how can the practice of strategic planning become mainstreamed in the unique workplace that is higher education.